Suhu Permukaan Laut di Perairan Raja Ampat Provinsi Papua Barat - M Ali Ulat (Jurnal Airaha, 2012)
This journal discusses the surface sea water termperatures in offshore waters of Raja Ampat,West Papua province (Results Citra 2006-2008).retrieval of image data in August 2009 April 2010 on the islands of Raja.The results showed that the image of warmer sea surface temperatures in the wast season and transisi I cooler in summer while the east and transitional II.